Dampak Pandemi Covid-19 pada UMKM Warung Ritel Tradisional di Indonesia dan Strategi Bertahannya - Mujianto Mujianto; Muhammad Ramaditya; Maya Mustika; Hans H. Tanuraharjo; Ridwan Maronrong (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2021)
This study aims to determine the impact of the Covid-19 pandemic on traditional retail MSMEs from the operational and financial business side in Indonesia, to find out the role and support from the government and related parties (private and state-owned enterprises) to help traditional retail MSMEs survive during the pandemic. Covid 19 and knowing the strategy and direction of business transformation from traditional retail MSMEs in terms of financial operations and marketing strategies in order to be able to survive during the pandemic. Design This research is a survey (as primary data) of owners of traditional retail stalls using quantitative descriptive analysis method. The results of this study are that the Covid 19 pandemic has an impact on traditional retail MSMEs with a decrease in turnover of retail shops / stalls compared to the period before the Covid-19 pandemic of 63.98%. The condition of the adequacy of the retail shop/stall business cash compared to the operating costs of the business during the Covid 19 pandemic which was under 12 months as much as 84.37%. Traditional retail stalls stated that 73.55% had never received assistance from the Government as a result of Covid-19 and 88.37% stated that they had never received assistance from private companies during the Covid pandemic. The Financial & Operational Strategy carried out by Traditional retail stalls in order to be able to survive and continue to grow during the Covid-19 Pandemic is to carry out cost efficiency as much as 34.33% with the Marketing Strategy is to complete the products sold in small packages/ renceng/sachets as much as 33, 58% and do wholesale orders online as much as 32.83%. The projected turnover of traditional retail stall businesses in 2021 has decreased, confirmed by 64.54% with projected operating profits in 2021 experiencing a decrease of 65.66%.